(untitled) - Satō, Giei (Honolulu, 1973)
The daily life of the monastery is portrayed here in ninety-seven watercolor sketches. Drawn during his last years by the Zen monk Giei Sato, these sketches recollect his days as an unsui, an apprentice monk. With humor and steadfast warmth Sato depicts the day of leaving home and the day of returning; the rainy season and the snowy season; the chores, the celebrations, the days of cleaning, and the days of begging. Each of the charming drawings is enhanced by a brief description of the event portrayed, a touch of Zen teaching, or a note on monastic life.
Keywords: Đời sống tôn giáo và tu viện (thiền môn),Monastic and religious life (Zen Buddhism); Nhật Bản,Japan